Escolarização de alunos chineses: realidade e desafios de inclusão numa escola privada de educação básica no município de São Paulo - Ribeiro, Soraya Magnani Lobo Costa (2020)
The present research investigated the problem about schooling and inclusion of Chinese students from a qualitative and exploratory study, in a private school in São Paulo. The critical theoretical framework adopted made it possible to approach the historical aspects of Chinese migratory movements in Brazil, the status of immigrants and the right to education, public educational policies as well as the complexity of the field of migration and education studies. Regarding the methodological aspect, this study carried out bibliographic research, documentary research and field research. As a tool for data collection, two structured questionnaires were prepared for the study, with qualitative questions. The questionnaires were applied during the visit to the school to each of the actors who works in this school institution: maintainer, principal, secretary, coordinator and teachers in the segments of Early Childhood Education, Elementary School, Middle School and High School. The results obtained show a certain contradiction regarding the discourse about the inclusion of foreign / Chinese students in the classroom and the effective educational practices: on one hand, the management team that aims at school inclusion and guarantee the integral formation of the human being, and, on the other, the factual reality of teachers who deal with tensions related to educational practices with these students, such as the need to work with cultural diversity, the language barrier, the lack of language learning programs and / or courses of Portuguese Language, the lack of participation by family members, etc. Thus, the absence of public policies aimed specifically at guaranteeing the right to education of foreign students as well as the lack of pedagogical proposals and / or programs within the scope of the school under study reveals that there is still a lot to be done regarding the inclusion and education of these students in the country.